Comparative Analysis on Propagation Effects of Flight Delays: A Case Study of China Airlines - Weiwei Wu; Cheng-Lung Wu; Tao Feng; Haoyu Zhang; Shuping Qiu (Journal of Advanced Transportation)
This paper aims to capture the interdependency among the sequence of flight delays due to airline operations in airports, weather, and air traffic control conditions. A copula function is used to determine the distribution of delay sequence and examine the propagation effects. Using the actual data sourced from an airline in Asia Pacific region, it is found that flight delays could propagate to downstream airports/airlines, where the strength of delays was decreased, passed on, or increased. Considering the possible effects of increased delays under air traffic control or airline factors, scenarios that adjust flight schedules with additional buffer time were created and analyzed. Results show that, by adding buffer time efficiently, flight schedules can become more reliable.